Synthesis of novel titania nanoparticles using corn silky hair fibres and their role in developing a smart restorative material in dentistry - Afsheen Mansoor; Emaan Mansoor; Ezza Mansoor; Efrah Mansoor; Atta Ullah Shah; Uzma Asjid; João Filipe Brochado Martins; Sami Ullah Khan; Paulo J. Palma (Computational and Structural Biotechnology Journal)
Objectives: The oral healthcare sector is witnessing a significant increase in the creation of eco-friendly biomaterials intended to inflict minimal damage to humans and the environment, primarily due to the inadequacies of conventional synthetic restorative materials which have a short shelf life and are prone to instability. The main objective of this study was to synthesise cost-effective titania nanoparticles (TiO₂ NPs) from biowaste corn silky hair fibre. Methods: The titania nanoparticles (TiO₂ NPs) were characterised through x-ray diffraction; scanning electron microscopy; energy-dispersive spectroscopy; Fourier transform spectroscopy, and atomic force microscopy, as well as dynamic light-scattering to identify their phases, morphologies, dimensions, and chemical compositions. The nanoparticles were subsequently integrated into standard glass ionomer cement (GIC) to create innovative smart titania-enriched glass ionomer cement at multiple concentrations in the form of 4 × 4 × 1 mm blocks, which were evaluated for enamel shear bond strength, spectral mapping, and surface topography. Results: Confirmation was obtained that the newly synthesised TiO₂ nanoparticles, with a particle diameter of 24.17 nm and a pure rutile phase, displayed a spherical morphology and a smooth surface. Adding 5 % of these smart titania nanoparticles to GIC resulted in a substantial increase in its shear bond strength to enamel, which rose to 4.93 + 0.74 MPa, with a standard error of 0.23, and this change was statistically significant at p < 0.05. The material's sustainable surface characteristics were confirmed by the presence of increased Fluorine (6.46 %) and Titanium (0.79 %) alongside a decrease in the amounts of Aluminium (23.51 %), Silicon (20.01 %), Phosphorus (0.33 %), and Sulphur (0.09 %), as indicated by spectral mapping. Conclusion: This study developed eco-friendly and sustainable titanium dioxide nanoparticles from silky corn hair fibres. The addition of titania nanoparticles to conventional glass-ionomer cement resuledt in increased enamel shear bond strength and altered surface texture with higher titanium and fluorine content, making it a promising smart restorative material for dentistry. Clinical significance: A new smart material containing titania-enriched glass ionomer cement showed its ability to significantly improve enamel shear bond strength and extend its storage life. These eco-friendly biomaterials have considerable clinical potential to provide enhanced stability and performance in the oral environment.